Alternative is life - Lidin, Konstantin (project baikal, 2023)
The history of European architecture contains many examples of the search for a non-alternative, the only correct approach. For several centuries, the Greco-Roman ancient classics served as such an ideal model. The pictorial fantasies of the architect (in the “architecture parlante” of the eighteenth century), rationality of functionalism, the ironic mixing of styles in postmodernism, the biomorphic curved surfaces of parametricism, and so on, also claimed the role of the ideal. But all attempts to get rid of alternatives and find the only way were unsuccessful. Uncertainty and alternativeness are an integral and necessary attribute of a living and developing architecture.
Keywords: architecture; history; theory; style; alternative